The SAGE glossary of the social and behavioral sciences - Sullivan, Larry E. (SAGE Publications, 2009)
"The SAGE Glossary of the Social and Behavioral Sciences is the first attempt to combine and compare terminology in nine separate social and behavioral science disciplines: communication, economics, education, geography, media studies, political sicence, psychology, public administration, and sociology. This glossary is necessary because the social and behavioral sciences have expanded and diversified rapidly over the past century. Many of the terms in social science research carry different meanings depending on the discipline."--BOOK JACKET.